PAASCU preliminary survey of basic education program - De La Salle University, Manila (Animo Repository, 2019)
The Office of the Chancellor shared the announcement from PAASCU that the Basic Education program was eligible to apply for a Formal Survey one year after receipt of the report. Br. Bernard S. Oca FSC congratulated the members of the DLSU Integrated School community for the support that they have extended in making the PAASCU Preliminary Survey a successful one.